ANALISIS INOVASI PEMERINTAHAN DIGITAL VILLAGE DALAM PENINGKATAN PELAYANAN PUBLIK DI NUSA TENGGARA TIMUR - Gerry I. S. Banabera (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
Research focuses on analyzing digital village governance innovations in improving public services in Naikoten II Village, Kota Raja Distric, Kupang City. The Purpose of this research is to find out and analyze the the implementation of digital village innovations, factor influence, and strategies carried out in overcoming the inhibiting factors for the the implementation of digital village government innovations. The theory used is the theory of characteristics of innovation put forward by Everett M. The result of the research show that implementation of digital village innovation at Naikoten II village hasso far been able to improve public services by utilizing technologhy so as to create effectiviness and efficiency in give service. The inhibiting factors in implementing digital village government innovations in improving public services aare dependence on one computer staff / operator to operate a server computer; frequent tering occurs network demage and failure on the server thet disrupts service activities; still a lack of adjustment by some people so that it is still served by menually; the absence of a special budget from the region government; frequent rotation or mutation of employees who will affect the service process; and a discipline due to this innovation. Therefore the strategy that needs to be carried out by regional government is to build coorperation between the regional government and third parties for digital village innovation development in Naikoten II village and its application in other village sithin Kupang City government and develop a digital village designation plan to become a permanent government program as the standar for implementing the services of the villages of the Kupang City government